Implementation of Pancasila Educational Game Media for Strengthening the Nationalism Character of Indonesian Children in Malaysia - Yusuf Hanafi; Ade Eka Anggraini; Khusnul Khotimah; Diah Aulia Azizatur Rohmah; Oktaviani Adhi Suciptaningsih; Zativalen, Oriza Zativalen (Yayasan Ahmar Cendekia Indonesia, 2024)
A sense of nationalism is necessary not only for Indonesian citizens living in the country but also for those living outside Indonesia. This is needed to foster further a sense of nationalism and love for the country for Indonesian citizens living outside Indonesia, including Indonesian citizens living in Malaysia. The purpose of this community service activity is to strengthen the nationalism values of Indonesian citizens living in Malaysia by utilizing the Pancasila educational game media. The target of this activity is Indonesian children living in Malaysia. The method implemented in this activity is to provide socialization and training on the utilization/application of Pancasila Educational Game Media. Based on these activities, the results obtained showed that the children were enthusiastic in utilizing the Pancasila educational game media which helped improve their understanding of the values of nationalism by utilizing the Pancasila educational game media.